Competence for Male Circumcision by Health Workers According to Health Law - Asmin Sahari (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: Indonesia is a state of law, where almost all provisions must be contained in the legislation. In the health aspect, it is also inseparable from the legal aspect, one of which is circumcision. Circumcision is a medical and invasive procedure whose implementation and evaluation are monitored by experts and professionals. In this study, I raised several matters of health law in it, namely, Do All Health Workers Have the Competence to Perform Circumcision Actions according to health law? The purpose of this study was to determine the juridical aspects of the circumcision of boys by doctors at the service as well as liability in the event of a home or even death. This research method is normative juridical. This article describes various problems related to circumcision as well as legal aspects related to male circumcision. Based on the results of a literature study, the authority for circumcision in boys is only with doctors, this is evidenced by the 2012 Indonesian Doctor Competency Standards which become competency level 4A, namely, doctors can carry out circumcision actions independently. The authority for circumcision can be delegated from doctor to nurse through a mandate, provided that the recipient of the mandate is a competent person in the field of circumcision, so there needs to be an institution that issues circumcision competencies for the nurse so that doctors can only delegate authority to competent nurses.Keywords: Competence, Circumcision, Health Law Abstrak: Indonesia sebagai Negara hukum, dimana hukum semua ketentuan harus termaktum dalam perundang-undangan. Dalam aspek kesehatan juga tidak lepas dari aspek hukum, salah satunya adalah tindakan sirkumsisi. Tindakan sirkumsisi adalah tindakan medis dan bersifat invasif yang pelaksanaan dan evaluasi dipantau oleh tenaga ahli dan professional. Pada penelitian ini saya mengangkat beberapa isu hukum kesehatan didalamnya, yaitu Apakah Semua Tenaga Kesehetan Memiliki Kompetensi Melakukan Tindakan Sirkumsisi Menurut hukum kesehatan?Bagaimana Kewenangan Tenaga Kesehatan Dalam Tindakan Sirkumsisi Di Layanan kunjungan rumat ? tujuan penelitian ini adalah mengetahui aspek yuridis pada tindakan sirkumsisi anak laki-laki oleh dokter di layanan rumah serta pertanggungjawaban dokter apabila terjadi kecacatan atau bahkan kematian. Metode penelitian ini adalah yuridis normatif. Artikel ini menjelaskan berbagai permasalahan berkaitan dengan tindakan sirkumsisi serta aspek hukum yang berkaitan dengan layanan sirkumsisi laki-laki. Berdasarkan hasil studi kepustakaan, Kewenangan tindakan sirkumsisi pada anak laki-laki hanya ada pada dokter, ini dibuktikan dengan Standar Kompetensi Dokter Indonesia tahun 2012 yang menjadi komptensi tingkat 4A yaitu dokter mampu melaksanan tindakan sirkumsisi secara mandiri. Kewenangan tindakan sirkumsisi dapat dilakukan pelimpahan dari dokter kepada perawat melalui delegasi, dengan syarat penerima delegasi adalah orang kompeten di bidang sirkumsisi, sehingga perlunya ada lembaga mengeluarkan sertifikat kompetensi sirkumsisi untuk perawat sehingga dokter hanya dapat melimpahkan kewenangan kepada perawat yang berkompeten.Kata Kunci : Kompetensi, Sirkumsisi, Hukum Kesehatan